Patterning Techniques for Fabrication of Submicrometer Structures in Photoresist, III-V Semiconductors and PMMA - Pudis, Dusan; Kubicova, Jarmila; Suslik, Lubos; Skriniarova, Jaroslava; Martincek, Ivan; Novotny, Ivan (Communications - Scientific letters of the University of Zilina, 2010)
This paper presents experimental results in the field of planar periodic structures, their fabrication and analysis. We demonstrate techniques and experimental results of fabrication of two-dimensional periodic structures and their preparation in a thin photoresist layer, III-V semiconductors and PMMA – interference lithography using two coherent laser beams, nanoimprint lithography and lithography using nearfield scanning optical microscope.